Synthesis of mesoporous ribbon-shaped graphitic carbon nanofibers with superior performance as efficient supercapacitor electrodes. (1st December 2018) - Ma, Chang; Cao, Erchuang; Li, Junjing; Fan, Qingchao; Wu, Liqiang; Song, Yan; Shi, Jingli
Abstract: Mesoporous ribbon-shaped graphitic carbon nanofibers (MRCNFs) have been prepared by combination of electrospinning technique, template method and catalytic graphitization of transition metal. Transition metal Co, originated from Co(NO3 )2 ·6H2 O doped in spinning solution, serves as both template of mesopores and catalyst for graphitic structure. The microstructure of MRCNFs has been optimized by adjusting doping amount of Co(NO3 )2 ·6H2 O. The resultant MRCNFs present a relatively centralized distribution of 2–10 nm mesopores, modest specific surface area of 463 m 2  g −1 and pore volume of 0.575 cm 3  g −1 . In addition, considerable nitrogen- and oxygen-containing functionalities (2.88 at.% of N and 4.88 at.% of O) are detected on MRCNFs. In view of electrode materials for supercapacitors, as-obtained ribbon-shaped morphology, mesoporous structure, considerable surface heteroatom-containing functionalities and high graphitization degree synergistically enhance the electrolyte ion diffusion and electron conduction. In a three-electrode test system, the resultant MRCNFs electrodes exhibit high specific capacitance (228 F g −1 at 0.2 A g −1 ), rate capability (of 58% capacitance retention at 20A g −1 ) and excellent cycle stability(of 95% capacitance retention after 5000 cycles at 2 A g −1 ). Graphical abstract: Highlights: Mesoporous ribbon-shaped graphitic carbon nanofibers (MRCNFs) have been prepared. Co particles serves as template of mesopores and catalyst for graphitic carbon. With SSA of 463 m 2  g −1, MRCNFs present a capacitance of 228 F g −1 at 0.2 A g −1 .